(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
The first record of a fossil amphibian in Slovenia is a fragment of a rib. It was collected in the Lower Triassic of the Julian Alps, at the Studorski preval area. The carbonate succession of the Lower Triassic at Studorski preval is characterized by alternations of dolomite, limestone, marly limestone and marlstone with particular beds of oolitic limestone. The macrofauna found at the site indicates an Olenekian age. The bone fragment is a rod-like element with an expanded, complete articular end and a broken, narrow shaft with a finely pitted to radial surface texture. It is identified as the proximal portion of a rib of a temnospondyl amphibian, possibly of a capitosaur. The presence of an isolated temnospondyl bone in Lower Triassic strata in Slovenia is consistent with previous records of temnospondyls in marine Lower Triassic strata.